Agenesis of the corpus callosum in two brothers. Issue 6 (December 1983) - Wilson, W G; Kennaugh, J M; Kugler, J P; Reynolds, J F
Abstract : Two brothers with developmental delay and unusual cranial configurations were found to have agenesis of the corpus callosum (ACC) by CT scan. Six published families in which ACC occurred in the absence of extracranial malformations are reviewed. No single mode of inheritance can account for all of these familial cases. This family illustrates the value of CT scanning in evaluating children with developmental delay.